Reforming healthcare what's the evidence? - Greener, Ian (Policy Press, 2014)
Reforming Healthcare: What's the Evidence? is the first major critical overview of the research published on healthcare reform in England from 1990 onwards by a team of leading UK health policy academics.
Keywords: Great Britain. -- National Health Service -- Reorganization.